2008
DOI: 10.1016/j.mod.2008.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Wingless signaling initiates mitosis of primordial germ cells during development in Drosophila

Abstract: The germline cells of Drosophila are derived from pole cells, which form at the posterior pole of the blastoderm and become primordial germ cells (PGCs). To elucidate the signal transduction pathways for the development of embryonic PGCs, we examined the effects of various growth factors on the proliferation of PGCs. Up- and down-regulation of Wingless (Wg) in both of soma and PGCs caused an increase and a decrease in the number of PGCs, respectively. The Wg/beta-catenin signaling pathway began to occur in PGC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Our previous study showed that Wg initiates the reentry of PGCs into mitosis, and Dpp increases the number of female PGCs at the end of the embryonic stage (Sato et al, 2008). Overexpression of Dpp increased the number of PGCs at the pupal-adult transition stage (Zhu and Xie, 2003).…”
Section: Introductionmentioning
confidence: 94%
“…Our previous study showed that Wg initiates the reentry of PGCs into mitosis, and Dpp increases the number of female PGCs at the end of the embryonic stage (Sato et al, 2008). Overexpression of Dpp increased the number of PGCs at the pupal-adult transition stage (Zhu and Xie, 2003).…”
Section: Introductionmentioning
confidence: 94%
“…Wingless (WG) is present in PGCs by stage 16 of embryogenesis and WG signaling appears to regulate mitosis of PGCs in the developing male and female gonad (Sato et al, 2008). Thus, cell adhesion and a number of signaling pathways cooperate during formation of the male GSC niche.…”
Section: Male Niche Formationmentioning
confidence: 99%
“…Expression of a reporter of dpp signaling, dad-lacZ, is observed in all PGCs during larval stages and in the anterior PGCs at early pupal stages (Sato et al, 2010;Xie and Spradling, 2000;Zhu and Xie, 2003). Overexpression of dpp in late embryogenesis and during larval development causes an increase in PGC number, while reduction of DPP or a second TGFb ligand, GBB, results in a reduction in PGC number (Sato et al, 2008(Sato et al, , 2010. During early pupal stages, TGFb signaling regulates clonal expansion of GSCs for population of the niche, as mutation of the DPP receptor, Thickveins (TKV), reduces the mitotic potential of GSCs and their ability to clonally populate the niche (Zhu and Xie, 2003).…”
Section: Female Niche Formationmentioning
confidence: 99%
See 2 more Smart Citations